Peran Badan Usaha Milik Desa (BUMDes) Dalam Mendukung Kemandirian Ekonomi Warga Desa Balaroa Pewunu - Novita Novita; Muhammada Zeylo Auriza; Mohammad Ega Nugraha (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
This community service is carried out with the aim of being able to assist program planning in the village. one of which is the management of village-owned enterprises (BUMDes). This research focuses on the role of Village Owned Enterprises (BUMDes) in supporting the economic independence of the residents of Balaroa Pewunu Village. The research method uses a descriptive qualitative approach. Data collection techniques were carried out by observation, interviews and documentation. Furthermore, the analysis technique used is descriptive analysis, which provides a descriptive description of the findings. The results of the study show that BUMDes have a role in supporting village economic independence. The role of BUMDes is by increasing the standard of living which has implications for the growth and equity of the rural economy. Improving people's standard of living is carried out by developing a business selling plant seeds, plant fertilizers, and plant pesticides.